Analysis of electrical network vulnerability using segmented cascading faults graph. (January 2020) - Wei, Xiaoguang; Gao, Shibin; Huang, Tao
Abstract: To reveal the mechanism of fault propagation and temporal information between electrical network branches intuitively and vividly, we have proposed a fault chain-based cascading fault graph (CFG) that considers the topological, physical, and fault operational features from an overload mechanism perspective. The proposed CFG is used to construct metrics to identify vulnerable branches of an electrical network. Furthermore, because the vulnerable branch rankings change with the changing fault chain length, the ranking results' change rules are investigated. As a result, the branch vulnerabilities' characteristics are found to be different at different stages under sequential attacks. Inspired by the characteristics, the CFGs are divided into three sub-CFGs, based on load shedding threshold, to identify the vulnerable branches at different stages. The proposed method is used to identify the vulnerable branches of the IEEE 39- and 118-bus systems, and its effectiveness is validated by investigating load shedding of the systems under deliberate attacks.